Development Law in Law Enforcement: Effective Strategies in Dealing with Refugee Smuggling - albri labaka; Nikko Budiman (Universitas Negeri Semarang, 2025)
The complex issue of human smuggling and refugees presents challenges for law enforcement officials in Indonesia. This study analyzes the effectiveness of law enforcement against cases of smuggling of mania, especially refugees, from the perspective of development law theory. Normative juridical research methods with legal and conceptual approaches. The research results show that human smuggling has been regulated in a special regulation through Emergency Law No. 8 of 1995 and Law No. 9 of 1992 concerning Immigration. However, the two laws and regulations only regulate the issue of immigration violations, so it is not possible to ensnare perpetrators of human smuggling crimes. On the other hand, the government's response efforts through Law Number 6 of 2011 are still ineffective in tackling human smuggling. In the context of Development Law Theory, there are strategies for effectiveness in handling the enforcement of refugee smuggling laws in Indonesia in the future, namely The Importance of Regulatory Reform in Dealing with Refugee Smuggling, Discretion in Law Enforcement, Decisions Based on Morals and Social, and the Importance of International Cooperation in Handling Refugee Smuggling, as well as the Empowerment of Law Enforcement Officials